Simulasi CPR Masyarakat Awam di Kabupaten Tolitoli - Evie, Sova; Hasni, Hasni; Ra'bung, Alfrida Semuel; Azwar, Azwar (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Cardiac arrest is an emergency condition that can be life-threatening and result in death if not treated immediately. Cardiac arrest can occur in various locations, from those that cannot be anticipated (outside the hospital) to those that can be anticipated (for example; intensive care room). When there is a victim of cardiac arrest, people who are near the victim have a very big role in carrying out CPR quickly. Cardiopulmonary resuscitation is an important determinant in the survival of cardiac arrest victims. This is the basis that everyone must know and understand the basic life support needed if a cardiac arrest occurs. This community service activity aims to increase the readiness of the cloud community to carry out basic life support/cardiopulmonary resuscitation. Using lecture methods, question and answer, discussion and simulation. The target of this community service activity is ordinary people in Tolitoli Regency, totaling 65 people. From the results of the post-test carried out, there was an increase in knowledge from an average score of 25 during the pre-test, increasing to 75 during the post-test. It can be concluded that there is an increase in knowledge and skills in ordinary people after education and simulations are carried out.